Smart Cities Their Framework and Applications - Mohamed Kassim, Anuar; Al-Sharif, Lutfi (IntechOpen, 2021)
The development of smart cities is important and beneficial to a government and its citizens. With the advent of the smartphone, rapid and reliable communication between and among individuals and governments has become ubiquitous. Everything can be connected and accessed easily with the touch of a finger. Changes in mobile internet telecommunication systems allow for the advance of new urbanization using smart city development methods. The evolution of technology in Industry 4.0, such as the advancement of cutting-edge sensors utilizing the Internet of things (IoT) concept, has wide applications in developing various smart systems. This publication analyzes the interconnected cyber-physical systems inherent in smart cities, and the development methods and applications thereof.